Dry and Wet CO2 Capture from Milk‐Derived Microporous Carbons with Tuned Hydrophobicity. (2nd August 2020) - Pokrzywinski, Jesse; Aulakh, Darpandeep; Verdegaal, Wolfgang; Pham, Viet Hung; Bilan, Hubert; Marble, Sam; Mitlin, David; Wriedt, Mario
Abstract: Pore size distribution and surface chemistry of bio‐derived (milk) microporous dominated carbon "MDC" is synergistically tuned, allowing for promising carbon capture in a dry CO2 atmosphere and in mixed H2 O–CO2 . The capture capacity is attributed to the synergy of a large total surface area with an ultramicroporous and microporous texture (e.g., S tot 1889 m 2 g −1, S mic 1755 m 2 g −1, S ultra 1393 m 2 g −1 ), and a high content of nitrogen and oxygen heteroatom moieties (e.g., 5 at% N, 10.5 at% O). Tailored two‐step low‐temperature pyrolysis‐chemical activation is employed to take advantage of the intrinsic properties of the precursor, allowing for this unusual textural properties‐heteroatoms combination. For example, tested at 1 bar and 295 or 273 K, MDCs adsorb up to 22.0 and 29.4 wt% CO2, respectively. MDCs are also tailored to be hydrophobic, with CO2 /H2 O adsorption selectivity even after prolonged cycling. Maximum working capacities of 10.8 wt% for pure CO2 and 3.5 wt% for a flue gas simulant (15% CO2, 85% N2 ) are measured using temperature swing adsorption with dynamic purge gases, while being minimally affected by humid conditions. This work is directly aligned with the United Nation's Sustainable Development Goal 13, take urgent action to combat climate change and its impacts. Abstract : Pore size distribution and surface chemistry of bio‐derived (milk) microporous dominated carbons "MDCs" are synergistically tuned, allowing for record carbon capture in a dry CO2 atmosphere and unique CO2 /H2 O selectivity.